Designer’s office in Malaysia: comparative analysis on space planning and design issues - Awang, Arita Hanim; Denan, Zuraini (2015)

(untitled)
A person's work environment is very important. We spend nearly as much time at work as we do at home and even for some office workers, they spend more at their office than home. Improper office environments can cause major stress for workers. Understanding office design and environment issues can help give insight on improving the atmosphere at work. Interior designer’s office is the chosen typology for this research. Their offices should be the best examples in office design as they are the one who will be given a task to design their client’s offices. Hence, more space requirements for their offices also gives challenge in understanding the real issues of workspace design. The objective of this research is to investigate the conditions and problems of existing designer’s office in Kuala Lumpur within the scope of spatial arrangement, furniture and equipment provision. This research also attempts to get the user perception towards their existing workspace. For this purpose, a case study method is adopted. An observation of three selected designer’s offices are conducted by doing a site measurement, site observation and questionnaire survey method to gather data on the user perception towards their existing workspace.